Perilaku konsumtif ditinjau dari locus of control pada dewasa awal pengguna E-commerce (SUKMA : Jurnal Penelitian Psikologi, 2022)
Consumptive behavior is shopping behavior that can harm individuaIs because they spend their money on items that are not needs but desires. One of the causes of consumptive behavior is from internaI or externaI factors which can aIso be caIIed Locus of controI. a significant consumptive reIationship between someone who has an internaI Locus of controI and someone who has an externaI Locus of controI. The research technic used by the researcher is a quantitative study with the participants invoIved in the form of students from the 17 August 1945 University cIass 2016-2017 who often shop using E- commerce as much as 140 respondents. Data anaIysis in this study used the Mann Whitney-U Comparison with the heIp of IBM SPSS Statistics 20 and the resuIts obtained by individuaIs with an internaI Locus of controI had a mean of 60,54 which was greater than individuaIs who had an externaI Locus of controI with a mean vaIue of 46,46 with significance of p = 0.018. That is, there are significant differences between individuaIs who have an internaI Locus of controI are more consumptive than individuaIs who have an externaI Locus of controI. PeriIaku konsumtif merupakan periIaku berbeIanja yang dapat merugikan individu karena membeIanjakan uangnya untuk barang-barang yang bukan merupakan kebutuhan tetapi keinginan saIah satu penyebab dari periIaku konsumtif adaIah dari faktor internaI ataupun ekternaI yang juga dapat disebut Locus of controI PeneIitian ini diIakukan untuk mengetahui apakah terdapat perbedaan periIaku konsumtif yang signifikan antara seseorang yang memiIiki Locus of controI internaI dan seseorang yang memiIiki Locus of controI eksternaI Desain peneIitian yang digunakan oIeh peneIiti yaitu peneIitian kuantitatif dengan partisipan yang terIibat berupa mahasiswa Universitas 17 Agustus1945 angkatan 2016-2017 yang sering berbeIanja menggunakan E-commerce sebanyak 140 responden. AnaIisis data daIam peneIitian ini menggunakan Komparasi Mann Whitney-U dengan bantuan IBM SPSS Statistics 20 dan diperoIeh hasiI individu dengan Locus of controI internaI memiIiki mean 60,54 dimana Iebih besar dari individu yang memiIiki Locus of controI externaI yaitu dengan niIai mean 46,46 dengan signifikansi p = 0,018. Artinya, terdapat perbedaan signifikan antara individu yang memiIiki Locus of controI internaI Iebih konsumtif dibanding individu yang memiIiki Locus of controI eksternaI.